Investigation of selected key indicators of circular economy for implementation processes in sectorial dimensions - Marinko Škare; Beata Gavurova; Viliam Kovac (Journal of Innovation & Knowledge (JIK), 2023)
The main goal of this study is to investigate and to evaluate the selected indicators of the circular economy to advance the development of effective tools and policies regarding the circular economy system. This investigation is supported by the three research questions covering the topics of dependence of the circular economy on the use of reusable material, help with the reuse of circular material for economic sectors to establish a platform for effective policy development and implementation, and finally, the necessity of quantifying circular economy indicators to obtain an accurate picture of the circular economy sector relationships. The eight research hypotheses are considered, five of which are rejected. The gross investment of the circular economy sector in tangible goods in the both explored variants - expressed in the currency units also as the share of gross domestic product, circular economy sector value added at factor cost, the glass packaging waste recycling rate, the metallic packaging waste recycling rate, and the municipal waste act in the statistically significant way. The study applies a regression analysis technique with consistently validating test outcomes. The discussion section introduces the implications of the analytical outcomes with a potential of the setting current policies in the circular economy system and the construction of the new ones.
Keywords: Q28; Q58; 650; Circular economy; Circular material use rate; Biowaste; Recycling rate; Municipal waste; Construction and demolition waste; Glass packaging waste; Metallic packaging waste; Regression analysis; European Union